Spanish version of the Heart Failure Somatic Perception Scale (HFSPS v.3) – psychometric properties - Antonio-Oriola, Rosa; Juárez-Vela, Raúl; Czapla, Michal; Durante, Angela; Di Nitto, Marco; Benavent-Cervera, José Vicente; Saus-Ortega, Carlos; Navas-Echazarreta, Noelia; Cobos-Rincón, Ana; Tejada-Garrido, Clara Isabel; Santolalla-Arnedo, Ivan; Gea-Caballero, Vicente (Frontiers in Cardiovascular Medicine, 2023)
The Heart Failure Somatic Perception Scale (HFSPS) is an instrument that examine the existence and gravity of physical signs and symptoms in patients with heart failure, as well as early and subtle symptoms of HF that have clinical value, we aimed to translate and adapt the HFSPS from English to Spanish and evaluate the psychometric properties.Method: HFSPS translation and back translation were carried out according to the method established by of Beaton et al. A confirmatory factor analysis (CFA) was performed to test the factor structures. To assess criterion-related validity, HFSPS factor scores were correlated with Kansas City Cardiomyopathy Questionnaire (KCCQ) scores using the Spearman correlation method. The reliability of the internal consistency of the HFSPS was determined by calculating the Cronbach's alpha coefficient and the factor score determination coefficient.Results: Data from 173 patients with a mean age of 80.7 years (SD 9.1), women (51.1%), were analyzed. The majority (74.7%) were NYHA class II/III. The confirmatory factor analysis of four factors after eliminating one item showed fit indices close to the recommended indices: χ2 = 169.237, p<0.001, CFI=0.920, TLI=0.901, RMSEA=0.057 and SRMR= 0.061. Regarding the validity related to the criterion, all the scores of the HFSPS dimensions were correlated with all the scores of the KCCQ dimensions and were statistically significant. The reliability of the HFSPS factors of the coefficient of determination obtained scores of 0.73 for the dyspnea factor and early and subtle and lower for edema and chest discomfort with fewer items. Cronbach's alpha was acceptable for three of the scales > 0.71 and poor 0.52 for chest discomfort with two items. The internal consistency index based on the model was 0.850.The Spanish version of the HFSPS is a valid and reliable instrument that that would be feasible to use in clinical practice and research setting to evaluate in the perception of symptoms in patients with heart failure.